Remarks on the rigidity of CR-manifolds - ZAITSEV, DMITRI (NUMDAM, 2006)
A method is proposed to obtain examples of smooth CR-manifolds whose local stability group is neither a Lie group nor infinite-dimensional.
PUBLISHED
Keywords: Pure & Applied Mathematics